2018
DOI: 10.1097/ta.0000000000001770
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-derived stem cell treatment modulates cellular protection in both in vitro and in vivo traumatic brain injury models

Abstract: Adipose-derived stem cell treatment results in improved cell survival, decreased inflammatory marker release, and decreased evidence of neural injury. No difference in functional recovery was seen. These data suggest the potential for ASC treatment to aid in cellular protection and recovery in neural cells following TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Kim et al first assessed the benefits of ASCs implantation and injection in patients with knee osteoarthritis in 2015 [89,90]. Both investigations showed significant pain relief and the improvement of cartilage lesions in MRI images; however, ASCs implantation showed higher improvement index value than ASCs injection group after a 1-year follow-up trial [90]. The efficiency of ASCs injections in osteoarthritis did not associate with the dose of treatment.…”
Section: Processes In the Clinical Application Of Ascsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al first assessed the benefits of ASCs implantation and injection in patients with knee osteoarthritis in 2015 [89,90]. Both investigations showed significant pain relief and the improvement of cartilage lesions in MRI images; however, ASCs implantation showed higher improvement index value than ASCs injection group after a 1-year follow-up trial [90]. The efficiency of ASCs injections in osteoarthritis did not associate with the dose of treatment.…”
Section: Processes In the Clinical Application Of Ascsmentioning
confidence: 99%
“…Additionally, using ASCs has shown promising results on the treatment of neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), intervertebral disc, amyotrophic lateral sclerosis (ALS), multiple system atrophy [93], Parkinson and traumatic brain injury (TBI) [90,91,92,93,94]. However, the efficiency of ASCs therapy in those neural related diseases is still being investigated.…”
Section: Processes In the Clinical Application Of Ascsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlling the inflammatory response after injury can be thought as a target for the TBI treatment. Kappy et al have demonstrated that ASCs and its own secreting proteins downregulate the secretion of inflammatory factors and inhibit the inflammation in TBI [118120].…”
Section: The Prospects For Clinical Application Of Ascs In Neural mentioning
confidence: 99%
“…β -APP can be used as a marker for diagnosing nerve damage and assessing the severity of TBI [122]. In Kappy's experiment, inserting ASCs into TBI mouse maintains the β -APP concentration instead of making the concentration of β -APP continuously increasing [118]. It suggests that ASCs play a neuroprotective role in the TBI model.…”
Section: The Prospects For Clinical Application Of Ascs In Neural mentioning
confidence: 99%